METODE DAKWAH DALAM PEMBINAAN AKHLAK MAHASISWI DI ASRAMA PUTRI STIBA AR RAAYAH SUKABUMI JAWA BARAT - Hidayat, Tatang; Amalia, Sinta; Istianah, Istianah (Jurnal Al-Hikmah: Jurnal Dakwah, 2025)
The phenomenon of moral decay of adolescents, both boys and girls, is very alarming today. This country could lose the successor of leadership and the first madrasa for the next generation in the future because of the moral decay that occurs. To improve the state of moral crisis, a good da'wah method is needed by a preacher or da'wah institution. This study aims to analyze the method of da'wah in fostering the morals of female students in the STIBA Ar Raayah Sukabumi women's dormitory. In the process of collecting data, the author uses observation techniques, interviews, and literature review studies. This research is descriptive qualitative field research. The result of this study is that the visible da'wah method used in the STIBA Ar-Raayah women's dormitory is the Al Mauizah Al Hasanah method or good advice and the Al Qudwah Al Hasanah method or exemplary. The da'wah method used has a good impact on the behavior and habits of female students.